The work in the pandemic of the COVID-19: reading experiences - Itani, Alice [UNESP] (Rede Investigacao Condicoes Trabalho-ricot, 2020)
This text has the objective of analyzing the work experience in the pandemic of the COVID-19 outbreak. It is a reflection on studies, data and testimonies obtained from 15 professionals. The experience is analyzed on the process in the conditions of social existence, taking two important points, financial and economic survival. Reading is carried out on the collective experience and on testimonies of the professionals bring in the narratives in a context full of insecurity and fear in the face of the unknown explored by fear as an instrument of domination. The fragility and vulnerability, which is not new, is accelerated in the pandemic. It is identified by the working conditions, as an individual deliverer, an increase in the vulnerability of those in the care services, notably health professionals an in the slaughterhouses, where a high rate of contamination is present in addition to the precarious working conditions and number of accidents. For those in teleworking, its is identified a work densification in addition to the disorganization of daily life.
Keywords: experience; workers; COVID-19; survival; insecurity; fear